Legal Issues in Relation to Product Liability Defences in Malaysia under the Consumer Protection Act 1999 - Muhammad Hafiz, Mohd Shukri; Rahmah, Ismail; Ruzian, Markom (Primrose Hall Publishing Group, 2020)
Under product liability law in Malaysia, a manufacturer, producer, or seller can be held liable for any injury or property damage suffered by the consumer or third party as a result of a defective product. However, strict civil liability under product liability laws and its defences have been a subject for debate due to its legal impact on consumers. This study aims to analyse the types of defences available in law that can be applied by the defendant in product liability cases. This doctrinal study focuses on the legal provisions available in consumer law pertaining to strict civil liability. The data was gathered and analysed by way of content analysis and critical analysis of legal sources. The findings, mainly based on a study of the relevant statutory provisions and court cases, indicate that there are several contentious legal issues regarding the application of defences under product liability law. It is proposed that better defence alternatives under product liability laws should be formulated and this can be an area for future research in order to provide solutions to the problematic issues that currently exist in this area of law.